MASS POVERTY AS A CONCOMITANT FACTOR FOR INSECURITY IN NIGERIA - Ugochukwu Amadi, Felix; Chinwe Ahamefula, Georgenia (African Journal of Social and Behavioural Sciences, 2024)
This paper titled “Mass poverty as a concomitant factor for insecurity in Nigeria” begins with an introduction in which an exposition on insecurity in Nigeria was given. The study had a general objective as well as three specific objectives. A literature review on the nexus between poverty and insecurity was then performed. The reasons for mass poverty in Nigeria were X-rayed followed by insecurity. Conflict theory was adopted in building the theoretical framework for the study. This was followed by the research methodology. The study covered one state from each of the six-geopolitical zones and simple random and purposive sampling techniques were adopted. Both secondary and primary data were used for this study. The sample size for the study was 22,240 respondents, with 3822 in each state. The questionnaires were administered via Google Forms, and community groups were reached through WhatsApp with the help of group admins. From the fieldwork, 98.9% of the respondents blame bad and corrupt leadership for poverty in Nigeria. 89.92% blame the dependent nature of our economic and political systems for poverty in Nigeria. 94.2% of the respondents see the neglect of agriculture as being responsible for poverty in Nigeria while 92.1% of the respondents attribute a lack of basic infrastructure as being responsible for poverty in Nigeria. Additionally, 98.9% of the respondents agreed that good, visionary and transparent leadership at various levels of government will resolve poverty and insecurity in Nigeria while 94.4% of them agreed that eliminating corruption in Nigeria will help to resolve poverty and insecurity in the country. Some concrete recommendations were proferred at the end as panacea to the issues of mass poverty and insecurity in Nigeria.